Exploring A Strategic Links between Absorptive Capacity, Supply Chain Agility, It Capability and the Organizational Performance of Indonesian Manufacturing Firms - Nopadol Burananuth; Polamorn Tamprateep (International Journal of Supply Chain Management, 2019)
The present research attempts to discover this supply chain management as an important issue of strategic management research. This study particularly examines two important IT capabilities which are expected to have influence on firm performance, these capabilities are 1) IT assimilation, the ability to synchronize and diffuse the applications of information technology under business structure, and 2) flexible IT infrastructure, a well-developed and carefully planned technological foundation which provides basis for present as well as future applications to be developed. Based on the dynamic capability’s perspective and the view of a hierarchy of capabilities, the prime objective of the currents study is investigating the direct relationship between absorptive capacity, supply chain agility, IT capability and organizational performance in the Indonesian manufacturing firms. In addition to that the mediating effect of absorptive capacity and supply chain agility is also examined. Employing the survey-based methodology, the SEM-PLS technique is used to test the hypothesized relationships. So, current study has used SEM-PLS as statistical tool to answer the research questions raised in this study and research objectives envisaged in the current study. The findings of the study have provided support to the theoretical foundation and proposed hypothesis of the current study. Current study will be helpful for policymakers and practitioners in understanding the issues related to supply chain agility, IT capability, absorptive capacity and the firm performance. In author knowledge this is among very few pioneering studies on this issue.